Medicinska sestra v komunikaciji s slepim bolnikom/varovancem - Slabe, Damjan (Obzornik zdravstvene nege, 1999)
In the article, the authors present special features of communication with a blind patient/client in all phases of nurs- ing care. The nurse who is familiar and skilled in basic principles of communication with the blind can criate solid basis for communication of high quality. The authors stress the importance of warm human relationship, professional knowledge in knowledge of specific features of sensory perception of the blind (blind-born child or an adult who lost his/her sight later in life). With the establishment of qualitycommunication, positive experience of the blind is enabled while in a blind-born child integral development is stimulated. The role of the nurse andher integral approach in the frames of nursing care in offering support to the blind (child or adult) and his/her family is stressed.
Keywords: Blindness; bolniki; Communication; komunikacija; Nurse-patient relations; Nursing; slepi; slepota; zdravstvena nega